Adsorption and removal of crystal violet dye from aqueous solution by modified rice husk. Issue 4 (April 2022) - Homagai, Puspa Lal; Poudel, Rachana; Poudel, Sujan; Bhattarai, Ajaya
Abstract: An approach to removing crystal violet (CV) dye from aqueous solutions was investigated by introducing a xanthate group on charred rice husk. The newly prepared charred rice husk (CRH) and xanthated rice husk (XRH) were characterized by XRD, SEM, FTIR, and elemental analysis. A batch technique was used to adsorb CV dye in aqueous suspensions. Different adsorbent quantities, concentrations, pH, and contact times were investigated to find the effect of these parameters. The optimum pH for both CRH and XRH was found to be 10. The adsorption capacity of CV dye onto CRH and XRH was found to be 62.85 mg/g and 90.02 mg/g at pH10, respectively. Langmuir isotherms could be reasonably explained by the experimental data. Within 60 min, equilibrium was achieved. Similarly, the kinetic data are best suited to the pseudo-second-order model. In comparison to XRH with CRH, XRH was found more efficient and can be used as a feasible alternative for removing CV dye from aqueous solutions. Abstract : Adsorption isotherm; Bio-adsorbent; Crystal violet dye; Xanthated rice husk.